Self-medication for malaria and associated factors in Kakumiro District, Uganda, August 2023: implications for malaria management and mortality prevention - Marie Gorreti Zalwango; Richard Migisha; Bosco B. Agaba; Lilian Bulage; Benon Kwesiga; Daniel Kadobera; Alex Riolexus Ario (Malaria Journal)
Abstract Background In August 2022, an epidemiologic investigation into an outbreak of cases of black water fever, a severe and fatal complication of malaria, was conducted in Kakumiro District, Central Uganda. Findings revealed an association between self-medication and the development of severe malaria complications. Factors associated with self-medication for uncomplicated malaria were described for improved malaria management and prevention of malaria related mortality in Uganda. Methods A community-based cross-sectional survey was conducted in Kakumiro District in August 2023. Using multistage sampling, 592 households were selected. A semi-structured questionnaire was used to interview one participant per household about self-medication for malaria in a family member of any age who suffered from malaria 6 months prior to the interview. Data on demographics, socio-economic factors, health-seeking behaviour, self-medication and antimalarial storage at home were obtained. Modified Poisson regression model was used for multivariate analysis. Results Of the 592 participants interviewed, 368 (62%; 95% CI 58.2–65.9%) had self-medicated for malaria. Self-medication was significantly associated with household heads aged ≥ 35 years (adjusted prevalence ratio [APR]: 1.77; 95% CI 1.04–3.01); distances ≥ 5 km to the health facility (APR: 3.05; 95% CI 2.09–4.47), and storage of antimalarial drugs at home (APR: 2.21; 95% CI 1.36–3.59). Having malaria episodes ≥ 6 in the household within 6 months was protective (APR: 0.39; 95% CI 0.23–0.65). The major reason for self-medication was antimalarial stockouts at health facilities. Drugs used for self-medication were commonly known to 65% of the respondents and were bought from drug shops (75%). Although, 85% used the recommended drug for malaria treatment, the dose was inappropriate for 66% of the patients and despite the under dose, 85% of the patients recovered without hospitalization. Conclusion The common occurrence of self-medication for malaria and the high potential for malaria drug resistance and increased malaria mortality due to inappropriate treatment was demonstrated. Adequate antimalarial stock to health facilities, instituting policies prohibiting the sale of incomplete doses by drug shops, social behavioural change campaigns against drug storage in homes and sensitization of communities on the dangers of self-medication and the consumption of inappropriate doses could reduce self-medication practices and its eventual consequences.